Research on multi-variation coupling effect of heart-shaped dual phase Hy-Vo silent chain system. (May 2017) - Cheng, Yabing; Wang, Xiaopeng; Liu, Huan; Gao, Wang; Zhang, Junyue
Highlights: Benchmark apothem and positioning offset angle are designed, and the harmonic relationship between them is analyzed. The meshing design system of the dual phase Hy-Vo silent chain plate-sprocket-tool based on heart-shaped hole is built. The dynamics model of the dual phase Hy-Vo silent chain transmission system based on heart-shaped hole is built. The support for the parameter optimization and the multi-variation coupling effect of dual phase transmission Hy-Vo silent chain is provided. Abstract: Based on the theory of transmission that the Hy-Vo silent chain meshes with the sprocket, the meshing design system of the dual phase Hy-Vo silent chain link-sprocket-tool and the dynamics model of the dual phase Hy-Vo silent chain transmission system based on heart-shaped hole are built. The main design parameters of chain link, benchmark apothem and positioning offset angle, are designed and the harmonic relationship between them and the dual phase transmission system fluctuations is analyzed. The simulation analysis results show that the fluctuations of the dual phase transmission system are less than those of the single phase transmission system obviously no matter how the benchmark apothem and the positioning offset angle vary. Compared to the single phase transmission system, the angular velocity variation of the dual phase transmission system is smaller and the frequency is lower. In addition, the influence on fluctuation of Hy-Vo silent chain that the benchmark apothem and the positioning offset angle have is not a simple superposition, but the result of interaction. The research results of this paper will provide the support for parameter optimization of dual phase transmission Hy-Vo silent chain, and also provide some scientific basis for multi-variation coupling effect of the dual phase Hy-Vo silent chain system.